Post-COVID syndrome in adults: an overview - Scharf, Rüdiger Eberhard; Anaya, Juan-Manuel (Viruses, 2023)
This article provides an overview of various aspects related to post-COVID syndrome. Apart from its prevalence, symptoms and sequelae, risk determinants, and psychosocial implications, the pathogenesis of post-COVID condition is discussed in more detail. A focus on thrombo-inflammation in SARS-CoV-2 infection, the role of neutrophil extracellular traps, and the prevalence of venous thromboembolism is made. Moreover, COVID-19 and post-COVID syndrome in immunocompromising conditions, and the impact of vaccination on the prevention and treatment of post-COVID symptoms are reviewed. Autoimmunity is a hallmark of post-COVID syndrome, and, therefore, is another focus of this article. Thus, misdirected cellular and humoral immune responses can enhance the risk of latent autoimmunity in post-COVID syndrome. Facing the high prevalence of COVID-19 cases worldwide, it can be assumed that autoimmune disorders will increase globally over the next few years. Recent advances in identifying genetically determined variants may open the avenue for a better understanding of the susceptibility to and severity of SARS-CoV-2 infection and post-COVID syndrome.
Gesehen am 29.07.2024